A method for quickly determining the content of boron oxide and aluminum oxide in slag-coagulating agent for steelmaking
By using sodium hydroxide and potassium nitrate as alkaline melting treatment, combined with inductive coupling plasma atoms of plasma atoms to transmit spectrometers, solve the problem of inaccurate and low -efficiency measurement of boron oxide and aluminum oxide content in the residue agent, realized fast and fast efficiency, and achieved rapid rapid measurement. , Accurate test results.
Patent Information
- Application Number
- CN202111069023.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-09-13
AI Technical Summary
The prior art is difficult to accurately and quickly determine the content of boron oxide and alumina in the slag condensant for steelmaking, resulting in inaccurate detection results and low efficiency.
The use of sodium hydroxide and potassium nitrate is used as an alkaline melt. After the sample is treated with alkali melting, it is immersed with hydrochloric acid, and the solution is to be tested. Finally, it is determined by an inductive coupled plasma atom of the plasma atom.
The rapid and accurate determination of the content of alumina and boron oxide in the residue agent to avoid losing the problem of boron oxide due to high temperature volatilization, and the test results are more accurate and stable.
Smart Images

Figure CN113670897B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of chemical detection, and in particular to a method for rapidly determining the content of boron oxide and aluminum oxide in a slag-setting agent for steelmaking. Background Art
[0002] Slag coagulant is a kind of raw material commonly used by metallurgical enterprises for rapid slag coagulation and slag powderization prevention. In the process of steel smelting, when the slag is cooled to a certain temperature, it will be powdered and become powdered slag. Due to the slag powderization, the dust on the work site will increase greatly, which seriously endangers the occupational health of employees. Slag coagulant containing boron oxide can effectively prevent slag powderization. When coagulating slag, the slag coagulant is placed in a slag pot or slag tray, and then the slag is poured. The slag and the slag coagulant are mixed and reacted by the impact force and stirring of the slag flow; or when pouring the slag, the slag coagulant is sprayed into the slag to mix and react with the slag coagulant. During the reaction, due to the presence of B2O3 in the slag coagulant containing boron oxide, the boron oxide atoms are in a [BO4] tetrahedral state, which will promote the compact structure of the slag. The treated steel slag will not be powdered during and after the cooling process, thereby avoiding dust pollution and improving the working environment. The dosage of slag coagulant is generally 2-4% of the total weight of steel slag, among which the content of boron oxide, aluminum oxide, etc. directly affects the slag coagulant effect, which requires accurate analysis and control of the content of boron oxide and aluminum oxide in the slag coagulant. However, at present, most domestic steel companies mainly control the composition based on adjusting the production process ratio and settle the accounts based on the use effect. Moreover, the existing technology does not record the detection method of the corresponding components of the slag coagulant.
[0003] In the detection of similar refractory components, high-temperature sintering or treatment is generally used; because it is difficult to decompose the sample by acid dissolution, especially in the slag-setting agent of the present application, the B2O3 content is as high as 8-20%, and the Al2O3 content is as high as 15%. The boron oxide and aluminum oxide therein are both amphoteric substances, and part of the boron oxide and aluminum oxide exist in the form of solid solution (acid-insoluble boron oxide and acid-insoluble aluminum oxide), which is difficult to achieve sample decomposition by acid dissolution. For example, in the prior art "Study on the determination of trace boron oxide in protective slag by ICP-AES method", the pre-treatment stage did not fully consider the full dissolution of acid-insoluble boron oxide and aluminum oxide in the material, and only acid treatment was used, and the boron oxide and aluminum oxide could not be completely leached into the solution, resulting in inaccurate detection results of the boron oxide and aluminum oxide content. Other prior arts, such as "fluorine-containing slag-determination of boron oxide content-neutralization titration method" and "continuous casting protective slag-determination of aluminum oxide content-EDTA titration method", use wet manual operation, which is complicated to operate, has a long operation process, and the efficiency of separate detection of boron oxide and aluminum oxide is low.
[0004] The international standard (ISO21078:2008) uses anhydrous sodium carbonate as a flux to melt and decompose the sample at around 1000°C. However, during the determination of the slag coagulant by this method, boron oxide will be lost due to high-temperature volatilization, and the solid residue is difficult to desorb and leach, resulting in a significant decrease in the accuracy of the test results.
[0005] Therefore, in order to solve the problems of the prior art, it is urgent to invent a method suitable for quickly determining the content of boron oxide and aluminum oxide in a slag-setting agent for steelmaking. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of this application is to provide a method for quickly determining the content of boron oxide and aluminum oxide in a slag coagulating agent for steelmaking. The method uses sodium hydroxide and potassium nitrate to alkali-melt the sample, then leaches it with hydrochloric acid, and fixes the volume to obtain a solution to be tested, and finally uses an inductively coupled plasma atomic emission spectrometer for determination. The method can achieve rapid and accurate determination of the content of aluminum oxide and boron oxide in the slag coagulating agent to meet production needs.
[0007] The present application example provides a method for surface treatment of an iron crucible for alkali melting, including: sample treatment and measurement steps, specifically including:
[0008] 1) Sample processing:
[0009] 1.1) placing a sample to be tested and an alkali flux in a crucible and mixing them to obtain a mixed powder, wherein the alkali flux is composed of sodium hydroxide and potassium nitrate;
[0010] 1.2) placing the crucible in a furnace, heating it, melting the sample to obtain a molten product, and cooling it;
[0011] 1.3) The melt in the crucible is eluted with distilled water, and hydrochloric acid is added to the eluent to obtain an leaching solution;
[0012] 1.4) Transfer the leaching solution into a volumetric flask and add distilled water to make up to volume to obtain the solution to be tested;
[0013] 2) Determination: The solution to be tested is measured by an ICP spectrometer, and the corresponding boron oxide and aluminum oxide contents are obtained from the standard working curves of boron and aluminum according to the spectral line intensity measured by the sample.
[0014] The inventors found that by using sodium hydroxide and potassium nitrate as an alkali flux, the strong oxidizing property of potassium nitrate can be fully utilized to pre-oxidize the slag coagulating agent at low temperature, and the boron oxide is oxidized into borate and fixed, and when the mixed flux is melted, because of its low melting point (about 318°C), high-temperature alkali melting treatment is not required during the measurement process, and the loss of boron oxide due to high-temperature volatilization can be effectively avoided, and the test results are more accurate and stable. In addition, after the mixed flux of sodium hydroxide and potassium nitrate is used for treatment, the sample is easier to desorb and leach into a solution, which is easy to prepare the solution to be tested.
[0015] In a possible implementation scheme, the mass ratio of sodium hydroxide and potassium nitrate in the alkaline flux is 1.5:1 to 2.5:1 (for example, 1.8:1, 2.0:1, 2.2:1 or 2.4:1, etc.); in the alkaline flux, if the potassium nitrate content is too low, the boron oxide cannot be effectively oxidized into borate for fixation, resulting in part of the boron in the subsequent slag coagulant unable to be leached into the solution, affecting the test results; if the potassium nitrate content is too high, the slag coagulant sample is easily splashed and lost during processing, resulting in low test results.
[0016] In a possible implementation, in order to achieve complete sample conversion, the mass ratio of the sample to be tested and the alkali flux is controlled to be 10:1 to 30:1 (eg, 15:1, 18:1, 20:1, 22:1, 25:1 or 28:1, etc.).
[0017] In a possible embodiment, in step 1.1), the surface of the mixed powder after mixing is covered with a layer of sodium hydroxide. Covering with sodium hydroxide can prevent the sample from splashing and losing at high temperature, resulting in a low test result; preferably, the mass ratio of the sodium hydroxide covered on the surface of the mixed powder to the sample to be tested is 5:1 to 10:1 (for example, 6:1, 7:1, 8:1 or 9:1, etc.).
[0018] In a possible implementation, the crucible is an iron crucible.
[0019] In a possible implementation, in step 1.2), the temperature raising process is specifically:
[0020] The first heating stage: heating to 740-760°C (e.g., 745°C, 748°C, 750°C, 755°C, or 758°C) at 8-12°C / min (e.g., 9°C / min, 10°C / min, or 11°C / min, etc.), melting for 180-240s (e.g., 190s, 200s, 210s, 220s, or 230s, etc.);
[0021] The second heating stage: continue to heat up to 760-800°C (for example, 765°C, 770°C, 775°C, 780°C, 785°C, 790°C or 795°C, etc.), and melt for 120-130s (for example, 122s, 125s, 127s or 128s, etc.).
[0022] The inventors found that when the slag coagulating agent is subjected to alkali melting treatment, the temperature is raised in two steps, wherein, in the first step, the temperature is raised to 740-760°C and the melting and heat preservation treatment is carried out. At this stage, the strong oxidizing property of potassium nitrate can be fully utilized to pre-oxidize the slag coagulating agent at low temperature, so as to oxidize the boron oxide into borate and fix it, so as to facilitate the subsequent desorption and leaching; preferably, after the melting treatment, the furnace door is opened and the crucible is gently rotated to shake the melt. After the pre-oxidation treatment, the second step is continued to raise the temperature to 760-800°C and the melting and heat preservation treatment is carried out to achieve complete transformation and melting of the sample; preferably, after the second step of melting treatment, when the crucible is taken out of the furnace for cooling treatment, the crucible is gently rotated to solidify the melt on the inner wall of the crucible, so as to accelerate the cooling of the sample and facilitate the subsequent elution. The method can effectively realize the conversion of the slag coagulant through two-step temperature treatment, especially the low-temperature pre-oxidation treatment in the first step, which realizes the complete conversion of boron oxide into borate; and the whole reaction process is gentle, and the alkali melting temperature is low, which can effectively prevent the problem of low accuracy of the detection result caused by sample splashing and high-temperature volatilization of boron oxide.
[0023] In a possible embodiment, in step 1.3), the crucible is placed in a container pre-filled with cold distilled water, the melt is eluted, and the crucible is cleaned.
[0024] In a possible implementation scheme, in step 1.3), the concentration of the hydrochloric acid is 36-38 wt %. After the hydrochloric acid is added, it is neutralized until the eluent becomes clear. During the neutralization process, the melt is heated and boiled to accelerate the leaching. Preferably, the boiling time is 2-3 min.
[0025] In a possible embodiment, the slag-setting agent contains (wt%): 25-45% MgO (for example, 28%, 30%, 32%, 35%, 37%, 40% or 43%, etc.), 8-20% B2O3 (for example, 10%, 12%, 15%, 17% or 19%, etc.), ≤15% CaO (for example, 2%, 4%, 7%, 9%, 10%, or 13%, etc.), ≥5% SiO2 (for example, 6%, 7%, 9%, or 15%, etc.), ≤15% Al2O3 (for example, 1%, 3%, 5%, 6%, 7%, 10% or 13%, etc.).
[0026] Compared with the prior art, the present invention has the following effects:
[0027] 1) Compared with the existing method of using sodium carbonate as an alkali flux to melt and decompose the sample at about 1000°C, this application uses sodium hydroxide and potassium nitrate as alkali flux, which has low cost, low reaction temperature and higher efficiency;
[0028] 2) Compared with the existing method of using sodium peroxide as an alkali flux, the reaction is fierce, easy to splash, and the production and storage process of sodium peroxide is complicated, and there are many impurity elements; the alkali flux used in this application not only has a low reaction temperature, but also has a more gentle reaction, which is more conducive to on-site batch production and testing;
[0029] 3) Compared with the existing one-step heating alkali melting process, the present application adopts a two-step heating process, which can effectively realize the conversion of the slag coagulant, especially the first step of low-temperature pre-oxidation treatment, which realizes the complete conversion of boron oxide into borate, which is beneficial to the subsequent desorption and leaching;
[0030] 4) Compared with existing similar methods and standards, this application has a wider detection range and only uses conventional acid and alkali chemical reagents such as sodium hydroxide and hydrochloric acid, avoiding the use of strong oxidizing and corrosive reagents such as perchloric acid and sodium peroxide, which is energy-saving and environmentally friendly, while reducing harm to human health;
[0031] 5) The ICP-AES method is used to determine alumina and boron oxide in slag coagulant, with a wide linear range and less matrix effect. Interference can be eliminated by selecting characteristic spectral lines;
[0032] 6) The ICP-AES method is used to determine alumina and boron oxide in slag coagulant, with high sensitivity, low detection limit, good accuracy and precision, and stable and reliable results.
[0033] 7) The operation process is relatively simple, easy to implement, highly operable, and improves work efficiency;
[0034] 8) It has strong versatility and has certain reference and application value for the determination of existing slag-setting agents such as alumina, boron oxide and other main and trace elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a flow chart for determining the content of alumina and boron oxide in the slag coagulant of this application; DETAILED DESCRIPTION
[0036] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0037] The method for rapidly determining the content of boron oxide and aluminum oxide in the slag-setting agent for steelmaking of the present application is further described in detail below in conjunction with the examples.
[0038] <Example 1>
[0039] A method for quickly determining the content of boron oxide and aluminum oxide in a slag-setting agent for steelmaking:
[0040] 1.1 Sample quantity
[0041] Sample weight: 0.100g, weighed to ±0.0001g.
[0042] 1.2 Blank test
[0043] Carry out a blank experiment along with the test sample.
[0044] 1.3 Sample processing
[0045] 1) Place the sample (1.1) in an iron crucible, add 3g of sodium hydroxide and potassium nitrate (2:1), stir thoroughly and mix, then weigh 1g of sodium hydroxide to cover the surface;
[0046] 2) Place the crucible in a muffle furnace, heat it to 750°C at a rate of 10°C / min, melt it in a high-temperature furnace at 750°C for 240 seconds until the crucible turns red, open the furnace door, and gently rotate the iron crucible to shake the melt; then continue to heat it to 770°C, melt it for 120 seconds, then take out the iron crucible, and when taking it out, gently rotate the crucible to solidify the melt on the inner wall of the crucible, and cool it slightly;
[0047] 3) Place the crucible in a 250 mL beaker pre-added with about 80 mL of cold water, wash the melt, clean the crucible, add 37 wt% hydrochloric acid, neutralize until the solution becomes clear, boil on an electric furnace for 2 min, remove, and cool to room temperature to obtain an leaching solution;
[0048] 4) Transfer the extract into a 250 mL volumetric flask, dilute to volume with distilled water, and mix well;
[0049] 5) The liquid after volume adjustment is filtered with qualitative rapid filter paper into a clean, dry 150mL Erlenmeyer flask. The first filtrate is discarded and the remaining liquid is filtered into the Erlenmeyer flask. The filtrate is used for ICP analysis.
[0050] 1.4 Establishment of standard curves of aluminum oxide and boron oxide
[0051] 1) Preparation of aluminum oxide and boron oxide standard curve solutions:
[0052] In 6 iron crucibles, along with the sample treatment, transfer the test solution into a 250mL volumetric flask and add 0, 0.30mL, 0.50mL, 1.00mL, 2.00mL and 3.50mL of alumina standard solution (1000ug / mL) respectively, dilute to the scale with water and mix well.
[0053] In 6 iron crucibles, along with the sample treatment, transfer the test solution into 250mL volumetric flasks and add 0, 1.00mL, 2.00mL, 3.00mL, 4.00mL and 6.00mL of boron oxide standard solution (1000ug / mL) respectively, dilute to the scale with water and mix well.
[0054] 2) Working curve drawing
[0055] According to the operating procedures of the ICP spectrometer, the spectral intensities of Al and B in each bottle of standard curve solution were measured respectively, wherein the analysis wavelength of Al element was 396.152nm, and the analysis wavelength of B element was 208.957nm; the working curve was drawn with the spectral intensity of aluminum oxide and boron oxide as the horizontal coordinate and the mass fraction of aluminum oxide and boron oxide as the vertical coordinate.
[0056] The relative mass fractions of aluminum oxide and boron oxide in the standard curve solution, the standard working curve equation and the correlation coefficient are shown in Table 1 below.
[0057] Table 1 Standard working curve data
[0058]
[0059]
[0060] 1.5 Test results and verification test
[0061] 1) Method precision
[0062] According to the sample amount (1.1), weigh six portions of converter slag standard GSBH42012-94 (the standard sample contains 1.78% Al2O3 and no B2O3. For this standard sample, only the alumina content is measured), six portions of the slag coagulant JYP-2004270164 to be tested, and six portions of the slag coagulant Q13121 to be tested. After sample treatment (1.3), the solution to be tested is obtained. The analysis wavelength of the Al element is 396.152nm, and the analysis wavelength of the B element is 208.957nm. The spectral line intensity of the solution to be tested is measured on an ICP spectrometer. By comparing with the established standard working curve, the detection data of alumina and boron oxide are obtained. The relevant measurement results are shown in Tables 2 and 3.
[0063] Table 2 Precision experimental data of aluminum oxide results (%)
[0064]
[0065] Table 3 Precision experimental data of boron oxide results (%)
[0066]
[0067] It can be seen from Table 2 and Table 3 that the laboratory coefficient of variation CV of the Al2O3 and B2O3 contents in the converter slag standard sample and the slag coagulant determined by the ICP-AES method of the present application meets the requirements of Table F.2 in GB / T27404-2008.
[0068] 2) Accuracy
[0069] In the accuracy verification process, since there is no standard substance for slag coagulant at present, this application uses converter slag standard sample GSBH42012-94. After sample processing (1.3), a certain amount of aluminum oxide and boron oxide standard solutions are added respectively, and the measurement is carried out according to the operating procedures of the ICP spectrometer. The experimental results are shown in Table 4.
[0070] Table 4 Alumina content accuracy test
[0071]
[0072] Note: GSBH42012-94 is added with Al standard solution concentration (100 μg / ml).
[0073] It can be seen from Table 4 that the test value and theoretical value after preparing the quantitative alumina standard solution in the converter slag standard sample are in good consistency.
[0074] 3) Recovery rate
[0075] Two slag coagulants JYP-2004270164 and slag coagulant Q13121 were selected, and a certain amount of aluminum oxide and boron oxide standard solutions were added according to Tables 5 and 6 below to carry out a recovery rate experiment. The analysis results are shown in Tables 5 and 6.
[0076] Table 5 Alumina recovery test data
[0077]
[0078] Note: Add Al standard solution concentration (100μg / ml)
[0079] Table 6 Slag-coagulating agent boron oxide recovery test data
[0080]
[0081] Note: Add B standard solution concentration (1000μg / ml)
[0082] It can be seen from Tables 5 and 6 that the recovery rate of the method meets the requirements of the national standard GB / T 27404-2008 "Laboratory Quality Control Specifications for Physical and Chemical Testing of Food" for recovery rate tests (Table F.1).
[0083] 4) Method detection limit and method range
[0084] The blank solution was used for 10 repeated determinations, the standard deviation s was calculated using the Bessel formula, and then the MDL was calculated according to the formula MDL = k*s. The k value for this evaluation was 3, and the detection limits and detection ranges of the aluminum oxide and boron oxide methods are shown in Table 7.
[0085] Table 7 Detection limits and detection ranges of aluminum oxide and boron oxide methods (%)
[0086]
[0087] It can be seen from Table 7 that the detection limit and detection range of Al2O3 and B2O3 in slag-setting agent by this method can meet the detection requirements.
[0088] <Example 2>
[0089] The same as in Example 1, the slag coagulant JYP-2004270164 was selected; the difference from Example 1 is that in the sample processing step:
[0090] 1) Place the sample (1.1) in an iron crucible, add 1g of sodium hydroxide and potassium nitrate (2.5:1), stir thoroughly, and then weigh 0.5g of sodium hydroxide to cover the surface;
[0091] 2) Place the crucible in a muffle furnace, heat it to 760°C at 8°C / min, melt it in a high-temperature furnace at 760°C for 180s until the crucible turns red, open the furnace door, and gently rotate the iron crucible to shake the melt; then continue to heat it to 800°C, melt it for 130s, then take out the iron crucible, gently rotate the crucible when taking it out to solidify the melt on the inner wall of the crucible, and cool it slightly;
[0092] 3) Place the crucible in a 250 mL beaker pre-added with about 80 mL of cold water, elute the melt, clean the crucible, add 36 wt% hydrochloric acid, neutralize until the solution becomes clear, boil on an electric furnace for 3 min, remove, and cool to room temperature to obtain an leaching solution.
[0093] The spectral line intensity of the solution to be tested was determined by the same ICP analysis method as in Example 1. Compared with the standard working curve established in Example 1, it was found that the Al2O3 content was 1.78% and the B content was 3.73%.
[0094] <Example 3>
[0095] The same as in Example 1, the slag coagulant JYP-2004270164 was selected; the difference from Example 1 is that in the sample processing step:
[0096] 1) Place the sample (1.1) in an iron crucible, add 2g of sodium hydroxide and potassium nitrate (1.5:1), stir thoroughly, and then weigh 0.75g of sodium hydroxide to cover the surface;
[0097] 2) Place the crucible in a muffle furnace, heat it to 740°C at a rate of 12°C / min, melt it in a high-temperature furnace at 740°C for 200s until the crucible turns red, open the furnace door, and gently rotate the iron crucible to shake the melt evenly; then continue to heat it to 760°C, melt it for 125s, then take out the iron crucible, gently rotate the crucible when taking it out to solidify the melt on the inner wall of the crucible, and cool it slightly;
[0098] 3) Place the crucible in a 250mL beaker pre-added with about 80mL of cold water, elute the melt, clean the crucible, add 38wt% hydrochloric acid, neutralize until the solution becomes clear, boil on an electric furnace for 2.5min, remove, and cool to room temperature to obtain an leaching solution.
[0099] The same ICP analysis method as in Example 1 was adopted to measure the spectral line intensity of the solution to be tested, and compared with the standard working curve established in Example 1, it was detected that the Al2O3 content was 1.75% and the B content was 3.77%.
[0100] <Example 4>
[0101] Similar to Example 1, the slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing step: the surface of the mixed powder after mixing was not covered with sodium hydroxide.
[0102] After testing, the Al2O3 content was 1.63% and the B content was 3.58%. It can be seen that since the surface of the mixed powder was not covered with a layer of sodium hydroxide, some samples may have been splashed and lost at high temperatures, resulting in a low test result.
[0103] <Example 5>
[0104] Similar to Example 1, the slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing step: the mass ratio of sodium hydroxide to potassium nitrate in the alkali flux was 5:1.
[0105] After testing, the Al2O3 content was 1.70% and the B content was 3.68%. It can be seen that due to the low potassium nitrate content, boron and aluminum were not completely leached out during the slag coagulant sample treatment, resulting in a low test result.
[0106] <Example 6>
[0107] Similar to Example 1, slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing step: the mass ratio of sodium hydroxide to potassium nitrate in the alkali flux was 1:1.
[0108] After testing, the Al2O3 content was 1.65% and the B content was 3.70%. It can be seen that due to the high potassium nitrate content, boron and aluminum were not completely leached out during the slag coagulant sample treatment, resulting in a low test result.
[0109] <Example 7>
[0110] Similar to Example 1, slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing step: two-step temperature increase treatment was not adopted, and in step 2), after the sample was placed in the muffle furnace, the temperature was directly increased to 770°C.
[0111] After testing, the Al2O3 content was 1.78% and the B content was 3.64%. It can be seen that the lack of pre-oxidation of boron oxide resulted in the volatilization loss of boron, resulting in a low test result.
[0112] <Example 8>
[0113] Similar to Example 1, the slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing steps: in step 2), the temperature of the first heating stage is 400°C.
[0114] After testing, the Al2O3 content was 1.76% and the B content was 3.69%. It can be seen that due to the low pre-oxidation temperature in the first heating stage, the boron oxide pre-oxidation was incomplete and lost, resulting in a low test result.
[0115] <Example 9>
[0116] Similar to Example 1, the slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing steps: in step 2), the temperature of the first heating stage is 770°C.
[0117] After testing, the Al2O3 content was 1.76% and the B content was 3.65%. It can be seen that due to the excessively high pre-oxidation temperature in the first heating stage, boron oxide has volatilized, resulting in a low test result.
[0118] <Comparative Example 1>
[0119] Similar to Example 1, the slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing step, 3 g of sodium hydroxide was added in step 1), but potassium nitrate was not added.
[0120] After testing, the Al2O3 content was 1.72% and the B content was 3.66%. It can be seen that since potassium nitrate was not added to the alkali flux, boron was lost, resulting in a low test result.
[0121] <Comparative Example 2>
[0122] Similar to Example 1, the slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing step, 3 g of sodium peroxide was added in step 1), but potassium nitrate was not added.
[0123] After testing: Al2O3 content is 1.68%, B content is 3.70%. It can be seen that because sodium peroxide is used as an alkali flux, sodium peroxide is a strong oxidizing agent, the reaction is violent, and it is easy to splash and cause losses during the melting process, resulting in low test results.
[0124] <Comparative Example 3>
[0125] Similar to Example 1, the slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing step, 3 g of sodium carbonate was added in step 1), but potassium nitrate was not added.
[0126] After testing, the Al2O3 content was 1.70% and the B content was 3.66%. It can be seen that since sodium carbonate was used as the alkali flux, boron and aluminum were not completely leached out during the slag coagulant sample treatment, resulting in a low test result.
[0127] <Comparative Example 4>
[0128] Similar to Example 1, slag coagulant JYP-2004270164 was selected; different from Example 1, in the sample processing steps, 3 g of sodium carbonate was added in step 1), and potassium nitrate was not added, and in step 2), the temperature was increased in one step, the alkali melting temperature was 1000° C., and the melting time was 240 s.
[0129] After testing, the Al2O3 content is 1.76% and the B content is 3.70%. It can be seen that although the use of sodium carbonate as an alkali flux increases the alkali melting temperature, it also leads to the loss of boron, resulting in a low test result.
[0130] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for quickly determining the content of boron oxide and aluminum oxide in a slag-setting agent for steelmaking, wherein the slag-setting agent contains (wt%): 25-45% MgO, 8-20% B2O3, ≤15% CaO, ≥5% SiO2, ≤15% Al2O3; characterized in that: include: Sample processing and measurement steps include: 1) Sample processing: 1.1) placing a sample to be tested and an alkali flux in a crucible and mixing them to obtain a mixed powder, wherein the alkali flux is composed of sodium hydroxide and potassium nitrate; the mass ratio of sodium hydroxide to potassium nitrate in the alkali flux is 1.5:1 to 2.5:1; sodium hydroxide and potassium nitrate are used as the alkali flux, and the strong oxidizing property of potassium nitrate is used to pre-oxidize the slag coagulating agent at low temperature, so as to oxidize the boron oxide into borate and fix it; 1.2) placing the crucible in a furnace, heating it, melting the sample to obtain a melt, and cooling it; the heating process is specifically as follows: The first heating stage: heating to 740-760°C at 8-12°C / min, melting for 180-240s; by controlling the temperature to 740-760°C, melting and heat preservation treatment is carried out, and the strong oxidizing property of potassium nitrate is used to pre-oxidize the slag coagulant at low temperature, so as to oxidize the boric oxide into borate and fix it, so as to facilitate the subsequent desorption and leaching; The second heating stage: continue heating to 760-800℃, melting for 120-130s; 1.3) The melt in the crucible is eluted with distilled water, and hydrochloric acid is added to the eluent to obtain an leaching solution; 1.4) Transfer the leaching solution into a volumetric flask and add distilled water to make up to volume to obtain the solution to be tested; 2) Determination: The solution to be tested is measured by an ICP spectrometer, and the corresponding boron oxide and aluminum oxide contents are obtained from the standard working curves of boron and aluminum according to the spectral line intensity measured by the sample.
2. The method according to claim 1, characterized in that In step 1.1), the mass ratio of the sample to be tested to the alkali flux is 10:1 to 30:
1.
3. The method according to claim 1, characterized in that In step 1.1), the surface of the mixed powder is covered with a layer of sodium hydroxide.
4. The method according to claim 3, characterized in that The mass ratio of the sodium hydroxide covered on the surface of the mixed powder to the sample to be tested is 5:1 to 10:
1.
5. The method according to claim 1, characterized in that In the first heating stage, after melting for 180-240 seconds, the crucible is rotated to shake the melt.
6. The method according to claim 1, in step 1.2), during the cooling process, the crucible is gently rotated to allow the melt to solidify on the inner wall of the crucible.
7. The method according to claim 1, characterized in that In step 1.3), the concentration of the hydrochloric acid is 36-38 wt %. After the hydrochloric acid is added, the solution is heated and boiled for 2-3 min.
Citation Information
Patent Citations
Method for measuring boron arsenic bromine tungsten in geochemical sample by ICP-MS
CN110672707A